A GOD EXISTS. Issue 43 (29th March 2016) - Harrison, Gerald K.
Abstract : I argue that normative reasons (reasons to do and believe things) are powerful evidence that a god exists. Normative reasons are presupposed by all intellectual inquiry, yet it appears there is only one thing they could credibly be: the favourings a god is having of us doing and believing things. I anticipate some possible objections and show them to be confused or dogmatic.